Pengaturan Dosis Asap Cair Berbahan Baku Tempurung Kelapa Sebagai Bahan Penggumpal Lateks - Sarbaini, Andrevil; Edison, Rachmad; Delvitasari, Febrina (Jurnal Agro Industri Perkebunan, 2018)
In the processing of solid rubber, such as the manufacture of crumb rubber and rubber smoke sheet, one of the most important stages is the coagulation process using coagulant. The coagulation process is instrumental in determining for quality the rubber produced. Low quality of bokar is caused by farmers using coagulant which are not recommended. Because of that, it’s necessary to found the alternative coagulant that does not damage the quality and the price is relatively cheap. The purpose of this research is gets the best dosage of coconut shell liquid smoke for latex coagulation and to evaluate quality crepe rubber coagulum using coconut shell liquid smoke. The quality observed is dirt content, ash content, volatile matter, PRI, Mooney viscosity, and color index was implemented at PTPN VII, Way Berulu, Pesawaran District. The doses used were 0,1%, 1,5%, 2%, 2,5%, and 3%. The result showed that the most effective dose used in this research was 1% with quality approaching formic acid treatment. Keywords: coconut shell, formic acid, latex coagulant, liquid smoke